(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the critical role of Self Help Groups (SHGs) and microfinance in promoting sustainable development in India, focusing on their potential for poverty alleviation and community empowerment. SHGs have become a key instrument in the country’s financial inclusion strategies, particularly in rural areas, where traditional banking services are limited. Through the facilitation of savings, credit access, and mutual support, SHGs provide financial independence to marginalized groups, especially women, fostering both social and economic development. This case study delves into the mechanisms through which SHGs operate in India, highlighting their collaboration with microfinance institutions (MFIs) to drive sustainable growth. The study examines the dual impact of these groups: on economic fronts, such as increasing household income and creating entrepreneurship opportunities, and on social dimensions, including women’s empowerment and the development of social capital within communities. The research methodology involves qualitative and quantitative analyses, using both primary data from interviews with SHG members and secondary data from existing literature and reports. The case study assesses the sustainability of SHG-led microfinance initiatives, discussing the successes and challenges they face in different socio-economic settings. The paper concludes by offering policy recommendations to enhance the effectiveness and sustainability of SHGs in India’s developmental landscape. Ultimately, it argues that SHGs, when combined with microfinance, are a powerful tool for creating sustainable livelihoods and fostering long-term community development.